(untitled) (Research, Society and Development, 2021)
This article aims to present results of a bibliographic research about the importance of reading by the adolescent and young audience. This study aims to foment the incentive of this practice, so that the subjects better understand the world and themselves, becoming more humanized and happy. In the methodology, a bibliographic survey was carried out, followed by consultations with different reading sources. As a result, ideas were obtained from different authors that show that in literary reading there is a link between subjects and the application of human rights, as long as they act with protagonism and autonomy. It also shows an analysis as to the type of language intended for young audiences, nearness relationships close relations with them with reading, thus presenting some suggestions of works that can be read by teenagers, fulfilling the function, not only of having fun, but to present them with new ideas of living together in society. In addition, it shows the ease with which the Internet is occupying spaces in people’s lives, interacting in an invasive way between teenagers and young people, bringing news that delight, but also enslave; they´re modern adaptations that seduce, attract, facilitate, but require a lot of time, space and training from those involved. It was possible to conclude that reading is a topic very addressed by the authors, given its importance for human growth. It is hoped that these ideas will serve as inspiration for anyone who wishes to be a facilitator in the formation of a more reader world.